2018
DOI: 10.1007/s00535-018-1472-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic IRS1 and ß-catenin expression is associated with histological progression and overt diabetes emergence in NAFLD patients

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is a risk factor for type 2 diabetes. Our aim was to investigate the relationship between NAFLD and impaired glucose metabolism in terms of insulin receptor substrate 1 and 2 (IRS1 and IRS2) expression in the liver.MethodsLiver biopsy was performed at the University of Tokyo Hospital between November 2011 and March 2016 on 146 patients with NAFLD who were not being treated with any diabetes or dyslipidemia drugs. Among them, 63 underwent liver biopsy after an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…The findings of our literature survey confirmed the implication of the following: HSP90AB1 has been suggested as a possible biomarker in overweight and obese children with NAFLD [41]; HLA-B [42], CTNNB1 [43] and HSPA5 [44] are found to be abnormally expressed in NAFLD patients; CDKN1A polymorphism is associated with the development of human NAFLD [45]; TRAF1 has been also detected in NAFLD patients [46]; HSPB1 phosphorylation site has been differed between NAFLD cohorts [47]; SMAD4 was overexpresed in NASH patients [48]; SMAD2/3 phosphorylation and nuclear translocation documented in the liver of NASH patients [49]; RELA is well-known to cause inflammatory responses in NAFLD [50]; PIK3R3 has been proposed as an effective candidate target for the development of NAFLD [51]; GSK3B inhibition has been proposed as a possible therapeutic target to manipulate the NAFLD [52].…”
Section: Thsupporting
confidence: 84%
“…The findings of our literature survey confirmed the implication of the following: HSP90AB1 has been suggested as a possible biomarker in overweight and obese children with NAFLD [41]; HLA-B [42], CTNNB1 [43] and HSPA5 [44] are found to be abnormally expressed in NAFLD patients; CDKN1A polymorphism is associated with the development of human NAFLD [45]; TRAF1 has been also detected in NAFLD patients [46]; HSPB1 phosphorylation site has been differed between NAFLD cohorts [47]; SMAD4 was overexpresed in NASH patients [48]; SMAD2/3 phosphorylation and nuclear translocation documented in the liver of NASH patients [49]; RELA is well-known to cause inflammatory responses in NAFLD [50]; PIK3R3 has been proposed as an effective candidate target for the development of NAFLD [51]; GSK3B inhibition has been proposed as a possible therapeutic target to manipulate the NAFLD [52].…”
Section: Thsupporting
confidence: 84%
“…Moreover, expression of Irs1 was upregulated in mouse primary hepatocytes stimulated with recombinant Wnt3a, which can activate canonical Wnt/β-catenin signaling [ 187 ]. In immunohistochemical staining of liver biopsies from NAFLD patients, the staining intensities of β-catenin and Irs1 seemed to be positively correlated [ 188 ]. While downregulation of Irs2 accompanied by decreased gluconeogenic gene expressions was observed in both patients with simple steatosis and NASH, expression of FAS , a lipogenic gene, was not decreased and was strongly correlated with Irs1 expression in NAFLD, suggesting that selective insulin resistance via downregulation of Irs2 is present in the early stages of NAFLD in humans [ 165 ].…”
Section: How Is Hepatic Lipogenesis Increased Even In the Presence Of Hepatic Insulin Resistance?mentioning
confidence: 99%
“…Hence, IR and inflammation form a vicious circle, each condition promoting the other and accelerating the development of NAFLD and other metabolic disorders in the presence of lipotoxicity [107]. In both obese and lean subjects, high IR was found to be the most significant predictive factor for NAFLD [108], and research showed that serum insulin levels are firmly associated with ballooning and hepatic lobular inflammation [109]. The intricate relationship between IR, NAFLD, and T2DM is based on a vicious circle.…”
Section: Adipokinesmentioning
confidence: 99%